Extemporaneous formulations in Germany – relevance for everyday clinical practice. (11th May 2018) - Staubach, Petra; Salzmann, Stefan; Peveling‐Oberhag, Adriane; Weyer, Veronika; Zimmer, Sebastian; Gradl, Gabriele; Lang, Berenice M.
Summary: Background: Extemporaneous formulations broaden the spectrum of therapeutic options for topical treatment in particular and thus improve patient care. The latest amendment to the Regulation on the Operation of Pharmacies issued in 2012 brought about changes in prescribing and manufacturing practices. The aim of the present study was to assess the relevance of extemporaneous formulations in everyday clinical practice. Methods: We used data from the German Institute for Drug Use Evaluation (DAPI) to analyze the prescribing practice for compounded preparations in Germany between the fourth quarter of 2011 and the third quarter of 2014. In doing so, we determined the total cost associated with extemporaneous formulations covered by statutory health insurance funds in the outpatient setting. Results: Approximately three out of ten prescriptions (30.54 %) by German dermatologists during the observation period were extemporaneous formulations. While dermatologists make up only 2.7 % of physicians working in the statutory health care system in Germany, they prescribe more than half of all compounded preparations (53.6 %). Each dermatologist prescribed an average of 270.4 formulations per quarter; that number was 13.5 (1.3 %) for all other medical specialties. On average, 1, 983, 687 extemporaneous formulations overall (1.3 % of all prescriptions) were prescribed per quarter, corresponding to a total cost of € 40, 944, 982 (0.55 %). Conclusions: Apart from finished medicinal products, extemporaneous formulations play a key role in outpatient care. Based on the principles of evidence‐based and patient‐oriented medicine, the quality of compounded preparations and the prescribing practice of physicians (standardized vs. individual formulations) should be further investigated to optimize the quality of these preparations.